2012
DOI: 10.1590/s0102-311x2012001000011
|View full text |Cite
|
Sign up to set email alerts
|

Autoavaliação de saúde bucal: resultados da Pesquisa Mundial de Saúde - Atenção Básica em quatro municípios do Estado do Rio de Janeiro, Brasil, 2005

Abstract: A autoavaliação da saúde é um indicador subjetivo que combina componentes físicos, emocionais e do bem-estar individual e vem adquirindo papel importante na área da Saúde Pública, sendo utilizado na avaliação do estado de saúde da população geral. Este trabalho objetivou estudar os cuidados assistenciais e o estado de saúde bucal, incluindo a autoavaliação, utilizando dados de 1.871 indivíduos, com 18 anos ou mais de idade, entrevistados na Pesquisa Mundial de Saúde - Atenção Básica, realizada em quatro municí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
2
10
2
15
Order By: Relevance
“…While some studies agree with these findings indicating that the oldest individuals had a more negative oral health self-perception [12,13], other studies observe the contrary result. In a research performed with elderly aged from de 60 years, in which most (54.5%) of the participants were classified into low socioeconomic level, the oral health self-perception was considered as positive, even in low conditions of oral health.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While some studies agree with these findings indicating that the oldest individuals had a more negative oral health self-perception [12,13], other studies observe the contrary result. In a research performed with elderly aged from de 60 years, in which most (54.5%) of the participants were classified into low socioeconomic level, the oral health self-perception was considered as positive, even in low conditions of oral health.…”
Section: Discussionmentioning
confidence: 84%
“…Factors as low educational level, unemployment, long period since the last dental appointment, treatment requirements, lost teeth, dry mouth, and difficulty in eating are related to the negative self-perception [6,8,[12][13][14]. Other studies found that the positive oral health self-perception is associated with low ages, high income, higher educational level, low DMFT index and small time elapsed since the last appointment [4,11].…”
Section: Introductionmentioning
confidence: 97%
“…Os resultados mais importantes deste trabalho referem à análise da associação estatisticamente significante entre gênero e satisfação com a saúde bucal (p = 0,007), sendo que as mulheres estavam menos satisfeitas quando comparadas aos homens. Esses resultados corroboram os dados da Pesquisa Mundial de Saúde 16 . Bulgarelli & Manço 29 relataram maior satisfação com a saúde bucal entre os idosos mais velhos, mas sem associação significante com o gênero.…”
Section: Discussionunclassified
“…Além disso, sabe-se que um maior nível de escolaridade e renda favorece maior busca por informações de saúde e uma autoavaliação mais positiva da saúde 16,28 . Nesse contexto, esperava-se que as variáveis de disponibilidade de recursos estivessem associadas ao desfecho no modelo final.…”
Section: Discussionunclassified
See 1 more Smart Citation